Controle da pressão arterial em hipertensos acompanhados no âmbito da Atenção Primária à Saúde - Farias, Dyego Anderson Alves de (2014)
The systemic arterial hypertension (SAH) affects approximately one third of individuals worldwide and is considered one of the diseases more common in the Brazilian population. Due to its high prevalence, hypertension is seen as a major risk factor for cardiovascular disease. The main objective of the study was to evaluate the control of blood pressure (BP) in hypertensive accompanied (1 year, 2 years and 3 years) by the Family Health Teams (FHS) of João Pessoa (JP) and Campina Grande (CG) during the period 2009-2011. This was an observational, retrospective population-based cohort. The BP control was assessed by comparing the mean systolic and diastolic blood pressure of hypertensive PAs grouped by follow-up time in years, by analysis of variance (ANOVA) and Analysis of Covariance (ANCOVA). In another step the perception and knowledge of hypertensive (followed by three years in the city of JP) on the disease and treatment, using a qualitative approach based on the analysis of the Collective Subject Discourse (CSD) was evaluated. In monitoring groups and the two counties there was a profile of hypertensive women, elderly, white or brown, low schooling, retired with uncontrolled blood pressure. No significant differences between the mean systolic and diastolic APs for hypertensive municipalities JP and CG was observed, as well as no differences were found between the means of monitoring groups in years. Statistical evidence (p-value 0.0062) that the follow-up time is related to blood pressure levels were found. The analyzes suggest that the longer follow-up by the user, the less discrepancy (pressure levels) between control and no control of the PA. In the qualitative phase was observed on reasonable knowledge of hypertensive disease, the treatment and control forms. Despite efforts by the government and health teams, it was found that the control of blood pressure levels, and as a consequence, the reduction of morbidity and mortality have not yet reached adequate levels. Alert to the need to review and change in the tracking system of hypertensive as recommended by the Ministry of Health transcends easier access to the drug, ie to seek an effective follow-up treatment, prevention and control of complications associated with SAH.